Fecal Continence in Patients with Low Rectal Malformation After Anoplasty: Fecal Continence with Low Rectal Malformation - Baloch, Abdul Jabbar; Perveen, Shazia; Kumari, Nitu; Aslam, Sana (Pakistan Journal of Health Sciences, 2023)
Anorectal malformations (ARMs) affect between 1:2000-2500 births comprising a heterogenous spectrum of malformations that vary considerably in their anatomical characteristics, complexity, and functional prognosis. Occasionally, the diagnosis is delayed to later infancy especially in cases where the bowel outlet is stenotic but at or near the proper anal position. Objective: To determine the frequency of fecal continence in patients with low rectal malformation after anoplasty. Methods: This was prospective Cross-Sectional Study conducted at Department Pediatric Surgery, National Institute of Child Health (NICH), Karachi, Pakistan from September, 2020 to March, 2021. All patients who fulfilled the inclusion criteria and visited to NICH, Karachi were included in the study. Informed consent was taken from parents / guardians after explaining the procedure, risks and benefits of the study. Parents/Guardian of patients were asked to fill the study questionnaire containing the Kelly Scoring System to assess the status of fecal continence of the patients. All the collected data were entered into the proforma and analyzed on SPSS. Results: Out of 189 patients, 63% were male and 37% were female. Fecal continence was found in 71.4% patients, statically significant with Body Mass Index. Mean ± SD of age was 3.7 ± 1.5 days. Conclusions: It is to be concluded that fecal continence is a frequent finding of low rectal malformation. Patients with low rectal malformation should be worked up for the fecal continence after anoplasty.